THE CONSTRAINTS ANALYSIS OF IMPLEMENTING SCHOOL LITERACY MOVEMENT AT SDN 2 KALIBENING - Nashri Maulidah; Neni Dewi Anggraeni; Tria Mugi Safitri; Siti Fatimah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
School literacy movement is one of the efforts to increase students' interest in reading and writing, so it needs to be applied in elementary school. This study aims to analyze the constraints with regard to implementation of the school literacy movement at SDN 2 Kalibening, Karanggayam,  Kebumen. This research is a descriptive study with research subjects involving 1 principal, 3 classroom teachers (grade 4, 5 and 6) and 15 students (grades 4, 5 and 6) state elementary school 2 of Kalibening. The research instruments used were questionnaires and interviews. Data analysis technique uses qualitative descriptive. The results showed that: (1) School literacy movement was still focused on literacy aspects of reading textbooks, (2) Teachers were less maximal in assisting students when implementing school literacy movements, and (3) The lack of facility to support the school literacy movement.